Finding self-similar behavior in quantum many-body dynamics via persistent homology - Spitz, Daniel; Berges, Jürgen; Oberthaler, Markus K.; Wienhard, Anna (SciPost physics, 2021)
SciPost Journals Publication Detail SciPost Phys. 11, 060 (2021) Finding self-similar behavior in quantum many-body dynamics via persistent homology